Improving the Performance of Photocatalytic Hydrogen Production through Adjusting the Size of Defective Quantum Dots Co‐Catalyst Affected by Intramolecular Steric Hindrance on Thermal Stability of Functional Groups. Issue 10 (24th August 2022) - Lian, Cuifang; Yu, Zebin; Sun, Lei; Jiang, Ronghua; Hou, Yanping; Huang, Jun; Chen, Jianhua; Zhong, Tao; Chen, Huajiao; Fan, Ben
Abstract : Quantum dots (QDs) co‐catalysts have been extensively studied in the field of photocatalytic hydrogen production (PHP) due to their limited domain effect. However, how to adjust the size of QDs co‐catalysts remains a big challenge. Herein, Ni2 P QDs co‐catalysts are synthesized via phosphating metal–organic frameworks (MOFs). Due to the intramolecular steric hindrance on the thermal stability of functional groups: electron‐giving functional groups ‐NH2, ‐OH, and electron‐absorbing functional group ‐COOH, the electronic symmetry of organic ligands and the coordination with metal ions is affected, resulting in three sizes of Ni2 P QDs co‐catalysts in the phosphating process, and the smallest one has the highest interfacial charge injection efficiency and transfer rate. Meanwhile, the carbon defects of the carbon skeleton produced in the phosphating process, in which the band position is lower than the conduction band of the Zn0.5 Cd0.5 S (ZCS) catalyst, can effectively collect electrons and inhibit the recombination of photocarriers to a greater extent, and Ni defects adjust the internal electronic structure of Ni2 P QDs. The results of experiments and density functional theory calculations demonstrate that Ni2 P@ZCS has excellent electronic structure and electron transfer efficiency. Thus, the best PHP performance of Schottky junctions Ni2 P@ZCS is achieved with the combined efforts of QDs co‐catalysts and defects. Abstract : The steric hindrance effect is an effective means to tune the size of metal–organic framework‐derived quantum dots (QDs). Smaller QDs have higher interfacial electron transfer efficiency, while defects assist in electron migration and suppress carrier recombination. Thus, the best photocatalytic hydrogen production performance of Schottky junctions Ni2 P@Zn0.5 Cd0.5 S is achieved with the combined efforts of QDs co‐catalysts and defects.